1985
DOI: 10.1021/jm00146a015
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and biological activity of carboxylic acid replacement analogs of the potent angiotensin converting enzyme inhibitor 5(S)-benzamido-4-oxo-6-phenylhexanoyl-L-proline

Abstract: The carboxylic acid group on the proline of 1 was replaced by a phosphoric acid, a hydroxamic acid, and a tetrazole to give compounds 2-4, respectively. Testing of 2-4 as angiotensin converting enzyme (ACE) inhibitors gave I50 values of 100, 1.6, and 22 microM, respectively, compared to 0.07 microM for 1. A hydroxamic acid derivative of the ketomethylene pentapeptide analogue 18 was then synthesized. This compound, 17, had an ACE I50 of 0.011 microM compared to 0.0076 microM for 18. Oral administration of 10 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…Unfortunately, however, both reactive aldehydes, including chloral, that have a high affinity to water resulting in the corresponding hydrates, and water‐soluble aldehydes have been considered unsuitable for asymmetric syntheses to date 3h. In this report, the proline‐derived tetrazole catalyst 1 5, 6 displayed even greater catalytic activity and efficiency, which widened the substrate scope in the water‐assisted direct aldol reaction.…”
Section: Methodsmentioning
confidence: 86%
“…Unfortunately, however, both reactive aldehydes, including chloral, that have a high affinity to water resulting in the corresponding hydrates, and water‐soluble aldehydes have been considered unsuitable for asymmetric syntheses to date 3h. In this report, the proline‐derived tetrazole catalyst 1 5, 6 displayed even greater catalytic activity and efficiency, which widened the substrate scope in the water‐assisted direct aldol reaction.…”
Section: Methodsmentioning
confidence: 86%
“…Almquist and co-workers [98] produced a series of derivatives in which substitution of the chelating group of the ketomethylene tripeptide analogue was examined. It was found that the hydroxamic acid derivative was as potent as the most active compound in use (compounds 38 and 39, Table III).…”
Section: Ace Inhibitorsmentioning
confidence: 99%
“…These rules define pharmacophoric/active site anchor points, among which the distance map is defined, as shown in Figure 1. Figure 1 also defines a set of five distances [11][12][13][14][15], which captures the relative orientation among the four pharmacophoric anchors to generate an active site model including the zinc atom. To establish a means of evaluating whether or not two conformers are equivalent in distance map space, the distance maps are evaluated on a multidimensional grid.…”
Section: Defining a Distance Mapmentioning
confidence: 99%